Procedimiento para la determinación de los parámetros de operación y de diseño considerando la calidad del azúcar no centrífugo granulado (2022)
A procedure for the design of agro-industrial processes considering product quality is proposed. It is exemplified with a case study to produce non-centrifugal cane sugar at the artisanal level. Modeling and simulation are valuable tools for the adequate selection of operating parameters. For this purpose, cane juice with 5.35 pH and 12.55 °Brix were considered as process limits. For concentration, random values of pH 5.5 - 7, °Brix 89 - 93, and concentration time of 20 - 30 minutes were generated. In crystallization, random values of pH 5.5 - 7, °Brix 90 - 94, agitation time of 10 - 20 minutes, and temperature of 40 - 60 °C were generated. Ten batches equivalent to one day, 120 batches equivalent to one month, and 1560 batches equivalent to one year were simulated. The inclusion of quality attributes in the process design allowed reducing defective products, a Sigma level higher than 3 was obtained, the economic and financial indicators are positive when the color in ICUMSA units fluctuates between 9000 - 11000.